2009
DOI: 10.1590/s1980-57642009dn30300006
|View full text |Cite
|
Sign up to set email alerts
|

Does prevention for Alzheimer's disease exist?

Abstract: The prevention of Alzheimer’s disease is a growing public health concern amidst an ageing population. Meanwhile, there is no effective or curative treatment available where prevention could greatly reduce health costs. This review was based on reports of potential preventive factors, including modifiable lifestyle factors, as well as preventive pharmacological strategies. Although the present review was not systematic, the reports selected from PubMed using “Alzheimer’s disease” and “prevention” as key-words, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(35 reference statements)
0
2
0
4
Order By: Relevance
“…Less educated subjects can be at a higher risk for AD. 24 The participants in this study had high levels of schooling, which showed the importance of education in the preservation of cognitive functions objectively assessed in the CAMCOG evaluation. 25 High scores on the CAMCOG were reported by Aprahamian et al 26 whose study found new cut-off points on the CAMCOG test according to education.…”
Section: Discussionmentioning
confidence: 66%
“…Less educated subjects can be at a higher risk for AD. 24 The participants in this study had high levels of schooling, which showed the importance of education in the preservation of cognitive functions objectively assessed in the CAMCOG evaluation. 25 High scores on the CAMCOG were reported by Aprahamian et al 26 whose study found new cut-off points on the CAMCOG test according to education.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, anti-amyloidogenic activity promoted by resveratrol (present in red wine) also seems to occur. 28 - 35 …”
Section: Methodsmentioning
confidence: 99%
“…Um estudo realizado com 32 idosos divididos em grupo caso e grupo controle, demonstrou que antes da intervenção os grupos não apresentaram diferenças no desempenho dos testes cognitivos aplicados. Após 10 encontros, o grupo caso apresentou melhoras no desempenho dos testes cognitivos e nas queixas subjetivas de memória (BRUCKI, 2009). Outro estudo de intervenção realizado com 79 indivíduos com 40 anos ou mais concluiu que após 20 sessões de intervenção, houve melhora no desempenho dos testes de memória, redução dos sintomas depressivos e de ansiedade e nas queixas subjetivas de memória (GIL et al, 2015).…”
Section: Medidas Não-farmacológicas -Aspectos Preventivosunclassified
“…A literatura ressalta que as atividades físicas e de lazer, o consumo moderado de álcool, a dieta do mediterrâneo e a prevenção de obesidade e hipertensão arterial sistêmica também são fatores que podem contribuir para a prevenção das demências, ressaltando a importância de medidas de prevenção e promoção de saúde e a necessidade de controle eficaz destes fatores de risco mesmo em indivíduos com declínio cognitivo (BRUCKI, 2009(BRUCKI, , 2011.…”
Section: Medidas Não-farmacológicas -Aspectos Preventivosunclassified
See 1 more Smart Citation